IMPLICATURE USED BETWEEN TWO HOSTS WHEN SWITCHING AND MIXING THEIR LANGUAGES - WULANDARI, SRI (Language Horizon: Journal of Language Studies, 2014)
IMPLICATURE USED BETWEEN TWO HOSTS WHEN SWITCHING AND MIXING THEIR LANGUAGES Sri Wulandari Language and Literature Department, Faculty of Languages and Arts, Surabaya State University Wulanqiyudzz@yahoo.co.id Drs. Slamet Setiawan, M.A., Ph.D Language and Literature Department, Faculty of Languages and Arts, Surabaya State University Slametsetia@yahoo.com Abstrak Penelitian ini focus dalam meneliti implikatur yang digunakan antara dua pembawa acara ketika mereka mengalihkan dan mencampur bahasa mereka. Penelitian ini dilakukan karena untuk mengetahui perbedaan alih kode dan campur kode dalam bahasa yang digunakan oleh pembawa acara Bukan Empat Mata dan Hitam Putih serta implikatur yang muncul ketika berbicara. tujuan dari penelitian ini adalah, 1) Untuk mengidentifikasi tipe alih kode dan campur kode yang mengandung implikatur dalam Bukan Empat Mata dan Hitam Putih. 2) Untuk menganalisa tipe dari implikatur di dalam alih kode dan campur kode 3) Untuk mengetahui perbedaan dari implikatur dalam alih kode dan campur kode yang digunakan oleh pembawa acara di Bukan Empat Mata dan Hitam Putih. Teori yang digunakan dalam penelitian ini yaitu teori tentang Campur Kode dan Alih Kode oleh Janet Holmes dan Implikatur oleh George Yule. Deskriptif qualitative digunakan dalam penelitian ini untuk menjelaskan secara sistematis situasi atau secara factual dan akurat. Teori yang digunakan yaitu Miles dan Huberman. Penelitian ini menemukan bahwa Tukul Arwana lebih sering menggunakan Campur Kode dalam mengubah pelafalan.. Sedangkan Deddy Corbuzier menggunakan selipan campur kode dalam percakapannya. Kata Kunci: Alih kode dan Campur Kode, Implikatur, Sosiolinguistik Abstract This study investigates Implicature Used Between Two Hosts When They Switch And Mix Their Language. This study is conducted because of the differences Code switching and Code mixing in the language used by the hosts of Bukan Empat Mata and Hitam Putih program and the implicature appear in their speech. The purposes of this study are, 1) to identify the types of code switching and code mixing contain of implicature appears in Bukan Empat Mata and Hitam Putih programs. 2) to analyze the type of implicature in code switching and code mixing. 3) to know the differentiate of implicature of code switching and code mixing used by hosts in Bukan Empat Mata and Hitam Putih programs. The theories used by this study are the theories about code mixing and code switching by Janet Holmes and implicature by George Yule. The descriptive qualitative research was used to describe systematically a situation or an area of interest factually and accurately, the theory of this research used Miles and Hubberman. This study found that Tukul arwana more often uses code mixing involving a change of pronunciation. While, the host of Hitam Putih, Deddy Corbuzier used insertion code mixing. Keywords: Code Switching and Code Mixing, Implicature, Sociolinguistics Relations INTRODUCTION People do not live alone. They live in a community which use more than one language. Language has a big role for their activity,because it fulfills their needs.People always communicate one another with language. Indonesia has many kinds of ethnics, customs, and languages, such as Madurese, Javanese, Betawinese, Sundanese, etc. So, most of Indonesian people are bilinguals. In modern era Indonesian people realize about the importance of English language. For this reason, they learn the language and try to speak it as fluently as they can. In our daily life, we often find people use different languages. Those differences include in many aspects, such as accent, dialect, speech also sex. And people have to select appropriate language with the condition to make the speech understood easily. used. Sometimes the languages are mixed or they are switched to another language in their speech or conversation. Then these phenomena are known as Code Switching and Code Mixing. When we listen to someone who is speaking, we normally try to understand not only the meaning of the words, but also what they intends to convey. Sometimes people convey their hidden message which lets the interlocutor think deeply to be able to catch the point of the message and the reason why the speaker says those words. It is known as Implicature (Yule,1996:35). Learning the meaning implied means we are learning pragmatics. Bukan Empata Mata is one of the talkshow programs in Trans7 guided by Tukul Rikwanto or also known as Tukul Arwana. He also used English when he becomes the host of this program, although he can’t speak English well. With his confidence, he always likes to use some English words. Every shows he usually has different theme about guest stars hobies, achievement, social live, love, etc. Those are combined with special characteristic of Tukul Arwana. The other program in the same channel, Trans 7, which is almost same as Bukan Empat Mata is known as Hitam Putih program. This program is a talkshow which is hosted by magician, Deddy Corbuzier Dedy often uses English words or utterances, and so does Tukul. So, the host of Bukan Empat Mata program named Tukul Arwana, and the host of Hitam Putih program named Dedy Corbuzier usually switches and mixes their language into some other language such as Indonesian, English, Sundanese, Javanese, etc, during their programs. In this study, the writer wants to understand about code switching and code mixing and the implicature in Talk show TV program. There are some reasons that make the writer interested to investigate Bukan Empat Mata and Hitam Putih program as the subject of the study. Based on the background of the study above, it is formulated the problems as follows: 1) What types of code switching and code mixing appear in Bukan Empat Mata and Hitam Putih programs?, 2) What kind of implicature that exists in code switching and code mixing used by the hosts inBukan Empat Mata and Hitam Putih programs?, 3) What are the differences between implicature of code switching and code mixing used by hosts in Bukan Empat Mata and Hitam Putih programs?. Referring to the research question, the purpose of this study formulated as follows: 1)To know the types of code switching and code mixing appears in Bukan Empat Mata and Hitam Putih programs. 2) To know the implicature that exists in code switching and code mixing used by the hosts in Bukan Empat Mata and Hitam Putih programs. 3) To know the differentiate of implicature of code switching and code mixing used by hosts in Bukan Empat Mata and Hitam Putih programs. In order to have good analysis, the study needs to be supported by related theories. The related theories in this study are the theories about Code Switching, Code Mixing, Implicature and Discourse in conversation. Those theories must be able to support the study on finding the answer for the satement of the problems. The phenomenon of bilingualism results in the occurence of code switching and code mixing (Wardaugh, 1986:101). Hoffman (1991:113) explains that code switching can occur quite frequently in an informal conversation among people who are familiar and have a shared educational, ethnic, and socio-economic background. It is avoided in a formal speech situation among people especially to those who have little in common factors in terms of social status, language loyalty, and formality. METHODE The method in conducting the study, is used the descriptive qualitative method. This section starts with the description of research design. Then it is continued with object of the study, instruments of the study, data and source of data, data collection technique, and data analysis technique. The subjects of this study are hosts in Bukan Empat Mata and Hitam Putih programs. The data of this study are obtained from the hosts’ utterance when they present the program of Bukan Empat Mata and Hitam Putih. Arikunto (2009 : 101) said that Instrument is toolthat choose to make the researcher systematic and easy in the process of collecting data.The researcher took a part as a instrument because she watched and listened then transcribe the data. This study used hosts’ utterances of the program of Bukan Empat Mata and Hitam Putih by Tukul Arwana and Deddy Corbuzier as the source of the data. In conducting data analysis in her research study the researcher uses some procedures and techniques. This study uses data analysis technique by Miles and Hubberman (1994:10). It presents some steps of how to analyze the data. 1) Data collection, Using observation and content analysis to collect data through transcribing and classifying. 2) Data reduction, Reduction the data that is not included in Data display. 3) Data display is an activity that engages the researcher to organize data. This is done in order to get conclusion and to find out the following steps that should be done. 4)Conclusion and Verification Stage, This phase is absolutely crucial toward the research study. It is a procedure that will approve the validity of data that have been collected. It is a stage where theories that have been collected in the second chapter are proven to be applied in answering the three research questions. DATA ANALYSIS AND DISCUSSION This section consists of result and discussion. It will analyze the data which has been collected. The result focuses on the data which is analyzed in order to be able to answer the first research question about types of code switching and code mixing appears in Bukan Empat Mata and Hitam Putih programs, the second research question deals with the implicature of code switching and code mixing used by hosts in Bukan Empat Mata and Hitam Putih programs, the third research question is the differentiate of implicature of code switching and code mixing used by hosts in Bukan Empat Mata and Hitam Putih programs. Then discussion is analysis obtained data uses theories which have been describe. Data 1. Utterances Type of Code Switching Type of Code Mixing Implicature GI PI Kamu keliatan malam ini cantik sekali dan saya liat kaki mu sexy. - Insertion code mixing - √ Table 1. The appearance of code switching and code mixing followed by implicature of Tukul Arwana’s utterance in Bukan Empat Mata In data number one The utterance which is uttered by Tukul above shows about insertion code mixing. Sexy is a word. The speaker insert an English word in Indonesian language through the sentence and the position of the English word is in the last of his utterance and continuing with Indonesian. From the form of sentence, the word sexy is an insertion of material (lexical item) which is from English language into Indonesia structure sentence. The sentence of the utterance is begun with Indonesian language “Kamu keliatan malam ini cantik sekali dan saya liat kaki mu” after that there was an English word sexy then, continuing to Indonesian language “Saya memang mengidolakan kamu tiap kamu ada di Televisi membuat saya tidak bisa tidur semalaman.” Tukul said that Cinta’s feet were sexy because she was wearing mini skirt. His feet looked desiring. Sexy is English word which is common used in daily conversation because if it is said in Indonesian word is too long. Sexy in Indonesian is “menggairahkan” or something desiring. The utterances imply that Tukul says the amazed and admired her guest. Implicature is the invisible meaning of an utterance that unsaid by the speaker (see appendixes 6). It kinds of particularized implicature because when Chyntia said that Tukul a playboy, he come to his guest star and persuade Cinta Laura. Utterances Type of Code Switching Type of Code Mixing Implicature GI PI Ya maksudnya minta tolong sama semkeriti yang disini - Code Mixing Involving a change of pronunciation - √ Table 2. The appearance of code switching and code mixing followed by implicature of Tukul Arwana’s utterance in Bukan Empat Mata Data above shows that Tukul’s utterance is mixed between English words and Indonesian pronunciation. This type of utterance belongs to code mixing involving a change of pronunciation. This sentence begins by the Indonesia language “ya maksudnya minta tolong sama.” After that there is an English word semkeriti but he said unclearly. Then back again to Indonesian language which appeared in sentence “yang disini”. The position of the English word is also in the middle of Indonesian sentence. Semkerity here is to mention security. But, he changed into Indonesian pronunciation. Security is someone who keeps order of the place. This utterance occurs when the guest is Cristie Julia. She is an actress of Indonesia. The reason is being more informative. Tukul commended her that she was on time people. She asked with joke that she came early to help security open the studio. Tukul knows that the audience will understand the implication of semkeriti (see appendix 6) so he said this word unclearly. It make the audience needs some special knowledge to understand the meaning and it called particularized conversational implicature. Utterances Type of Code Switching Type of Code Mixing Implicature GI PI Aahhh kamu saya undang-undang katanya gak ada waktu gak ada jadwal gak ada schedule gak punya mobil. - Insertion code mixing √ Table 3. The appearance of code switching and code mixing followed by implicature of Deddy Corbuzier’s utterance in Hitam Putih The linguistic unit of “schedule” is a word. Deddy inserts a word in English language through the sentence and the position of the English word is in the middle of the sentence. From the form of sentence, the word “schedule” is an insertion of material which is from English language into Indonesia structure sentence. It was began with Indonesian language “Aahhh kamu saya undang-undang katanya gak ada waktu gak ada jadwal gak ada” after that there was an English word “schedule” then, back again to Indonesian language which appeared in the sentence “gak punya mobil” . From data above, Deddy’s utterance is about invitation for Syahrini, he mixed his Indonesian language with schedule. Deddy showed in his utterance that he felt hard to invite Syahrini in his Talk Show. As we know, Syahrini is famous actress with many kinds of jobs on air and off air. To meet her, someone should make a schedule. In Indonesian schedule is jadwal. This type of Deddy’s utterance is insertion code mixing, because this kind of code mixing . From data above Deddy expressed implicit meaning that Syahrini is a busy person and she doesn’t have a car but the fact is she has many kinds of luxurious cars and it’s type of generalized conversational implicature. Code switching and code mixing often happen in conversation of Tukul Arwana and Deddy Corbuzier. The result above has different type of code switching and code mixing between Tukul Arwana in Bukan Empat Mata program and Deddy Corbuzier in Hitam Putih program Discussions As has been explained in the result section, Tukul Arwana and Deddy Corbuzier have different type of code switching and code mixing. They are mixing of linguistic elements from two different languages, Indonesia and English language. Tukul Arwana did almost all of type of code mixing. Code mixing is kind of several types. Tukul used kind of code mixing involving a change of pronunciation where he changes the correct pronunciation into his own idea of pronunciation. It usually different with original English pronunciation. He cannot speak English well but he confident to speak in front of audience with his style although his pronunciation was not correct. The other hand is about insertion code mixing. Deddy corbuzier more often use this type than Tukul Arwana Dedy deliver the English utterance without false pronunciation because when he was young he went to abroad to study about something. Based on these explanation above, it can be concluded that Types which usually used by Tukul Arwana and Dedy Corbuzier was different. Type code mixing of Tukul Arwana is Code mixing involving a change of pronunciation while Deddy is Insertion code mixing which is inserting English words into Indonesian sentences. CONCLUSION AND SUGGESTION Conclusion Based on the result,it can be concluded that host in Bukan Empat Mata and Hitam Putih are bilingual persons. They can speak other languages besides Indonesian. Sometimes Tukul Arwana or Deddy Corbuzier switch and mix their language. From the code switching and code mixing contain of implicature. Tukul Arwana and Deddy Corbuzier have different type of code switching. Suggestion Considering explanation above, the writer expects that this study is able to enrich to enrich sosio-pragmatic studies. Especially about implicature in code switching and code mixing. The writer hopes this study is able to give some information in understanding about implicature in code switching and code mixing. For the reader, the writer expects this study can be usefull and can be one of the references to understand about implicature in code switching and code mixing. Hopefully there will be other researchers who will follow-up this topic with new findings and they can give more explanation in details from different points of view. REFERENCES Arikunto, Suharsimi. (2006). Prosedur Penelitian. Jakarta: Rineka Cipta Blom, Jan-Petter; John J. Gumperz (1972). "Social meaning in linguistic structures: Code switching in northern Norway". In J. J. Gumperz and D. Hymes. Directions in Sociolinguistics. New York: Holt, Rinehart, and Winston. Bogdan, C and Biklen Knopp 2000. Qualitative Research for Education. Boston : Advison of Sinn and Schuster. Inc Brown, G. and Yule, G. 1983. Discourse Analysis. Cambridge: Cambridge University Press. Charlotte, Hoffman. 1991 An Introduction to Billingualism. Amazon Press Cutting, Joan.2002 Pragmatics and Discourse. London : Routledge Grice. 1975. “Logic and Conservation”, Logic and conservation studies in syntax ans semantic III: Speech act . In cole and Morgan 1975 : 41 – 58. New York : Academic Press Holmes, Janet. 2001 . An introduction to Sociolinguistics. England : PearsonEducation Leech, Geoffrey. 1983. Principle of Pragmatics. England: PenguinBook Levinson, Stephen C. 1983. Pragmatics. Cambridge: Cambridge University Mey, Jacob L.1993 Pragmatics : An introduction. Canmbridge: Blackwell Miles, M. B., & Huberman, A. M (1994).An Expanded Sourcebook Qualitative Data Analysis.Thousand Oaks, CA: Sage Publications Mill,Sara. 2004. Discourse. London : Routledge Muysken, P. (2000). Bilingual Speech A Typology of Code Wardhaugh, Ronald 1986 .An Introduction to linguistic. Cambridge: Cambridge University Press. Yule, George. 1996. Pragmatics. New York: Oxford University Press Http://www.Twitter.com/@bukan4mata Http://www.Twitter.com/HitamPutihT7 Http://www.Facebook.com/BukanEmpatMata Http://www.Facebook.com/HitamPutihTrans7 Http://www.Wikipedia.com.